Analisis SDM, Komitmen Organisasi, dan Motivasi Kerja Terhadap Kinerja Pegawai Pada Dinas Perindustrian dan Perdagangan Kabupaten Tulungagung - Sryningsih Sryningsih (Universitas Islam Kadiri, 2020)
This study aims to: (1) To find out and analyze the quality of human resources, organizational commitment, work motivation partially / individually significant effect on employee performance at the Department of Industry and Trade of Tulungagung Regency; (2) To find out and analyze the quality of human resources, organizational commitment, work motivation partially / individually have a significant effect on the performance of employees at the Tulungagung Regency Industry and Trade Office; (3) To find out and analyze the quality of human resources, organizational commitment and work motivation which has a dominant influence on employee performance at the Tulungagung District Industry and Trade Office. This research was conducted at the Department of Industry and Trade of Tulungagung Regency with all respondents as many as 43 employees. Data collection using questionnaires and documentation. Data analysis techniques using multiple linear regression with the help of SPSS Software. The results showed that: (1) Quality of Human Resources, Organizational Commitment, Work Motivation simultaneously / jointly had a significant effect on the Performance of Employees at the Industry and Trade Office of Tulungagung Regency; (2) Quality of Human Resources, Organizational Commitment, Work Motivation partially / individually have a significant effect on the Performance of Employees in Tulungagung Industry and Trade Office; (3) Quality of Human Resources, Organizational Commitment and Work Motivation have a positive and significant effect jointly on employee performance in the Tulungagung Industry and Trade Service and the most dominant variable influencing the Employee Performance in the Tulungagung Industry and Trade Service is the variable Quality of Resources Human.